Event-Triggered Saturation-Tolerant Prescribed Control of Rigid Spacecraft With Actuator Faults - Cheng, Peng; Luo, Wenjun; Liu, Chenjun; Li, Jiacheng; Liu, Jason J. R.; Li, Dapeng; Liu, Yan-Jun (IEEE transactions on circuits and systems. I, Regular papers, 2025)
This paper introduces an event-triggered saturation-tolerant prescribed control (STPC) framework for rigid spacecraft subject to actuator faults and actuator saturation via a fixed-time disturbance observer (FTDO). An FTDO with time-varying observer gains is initially developed to reconstruct the lumped perturbations caused by external disturbances, parameter uncertainties, and actuator faults. A fixed-time auxiliary system is employed to counter the adverse effects of actuator saturation. Additionally, asymmetric prescribed performance and shift functions are skillfully incorporated to handle arbitrary bounded initial conditions. Subsequently, a novel FTDO-based event-triggered STPC strategy is formulated, ensuring that attitude-tracking errors converge to predefined performance bounds within a predetermined time while minimizing unnecessary control signal updates. The practical fixed-time stability of all closed-loop signals is validated, with the strict avoidance of Zeno behavior. Finally, simulation studies are conducted to verify the accuracy and effectiveness of the proposed approach.